ISOLATION AND CHARACTERIZATION OF DETERGENT STABLE LIPASE FROM HALOPHILIC BACTERIA Halomonas eurihalina BK-AB15 - Rizki Pangesti, Ertanti
The use of enzymes as biocatalysts in a variety of industries has increased rapidly. One of the biocatalysts is a lipase that acts as a biocatalyst in the hydrolysis reaction of long-chain triacylglycerol into free fatty acids and glycerol. Lipase applied to a variety of industries, including food industry, paper industry, cosmetics, detergents, biodiesel, biotechnology, and others. Variations in the application raise the need of lipase with certain characteristics, such as resistance to alcohol, organic solvents, high salinity, detergents, and high temperatures. This condition prompted to search other sources of lipase in various extremophile microorganisms in extreme habitat conditions. In this study, lipase isolated from Halomonas eurihalina BK-AB15, halophilic bacteria, which is able to live in high salinity environment. Halomonas eurihalina BK-AB15 comes from the source of brine mud crater "Bledug Kuwu" located in the village Kuwu Kradenan, Purwodadi, Central Java. Lipolytic potential of H. eurihalina BK-AB15 shown by fluorescent in orange colonies, when the bacteria are grown on solid medium containing rhodamine B. Lipase is produced in a liquid medium containing 0.5% peptone, 0.5% yeast extract, 0.05% CaCl2, and NaCl 8%. The crude extract of lipase was fractionated using ammonium sulfate 0- 30%, 30-60%, and 60-70%, wherein the fraction with the highest specific activity was obtained in 60-70% fraction. Native PAGE and zymography showed that the best fractions containing only one kind of lipase, with a molecular weight of 39 kDa resulted by SDS-PAGE characterization. Lipase has optimum activity at pH 9.5 and 45 oC. This enzyme activity was influenced by metal ions, where the addition of Ca2+, Mg2+ and Ba2+ gave effect to the increase in activity, while the addition of Zn2+, K+, and Ni2+ gave opposite effect. Because the effect of Ca2+ addition was more prominent in enhancing lipase activity, we further evaluated this effect toothers parameters, such as pH and temperature optimum, variations of NaCl concentration, inhibitor, organic solvents, variations of SDS concentration, and thermal stability. The addition of Ca2+ did not affect the pH and temperature optimum of lipase. Metal ion chelator, such as EDTA did not significantly decrease the activity, so that this enzyme may not belong to the group metalloenzim. On the